2009
DOI: 10.1029/2009gl039851
|View full text |Cite
|
Sign up to set email alerts
|

Radial and latitudinal gradients of anomalous cosmic ray oxygen in the inner heliosphere

Abstract: We use data from the Ulysses, Advanced Composition Explorer, and Solar Terrestrial Relations Observatory spacecraft to determine the radial and latitudinal gradients of anomalous cosmic ray oxygen in two energy ranges from 4.5–15.6 MeV/nuc in the inner heliosphere for the first time during an A<0 part of the solar cycle. Using measurements from early 2007 to mid‐2008, we find that the radial gradient is ∼48 ± 13%/AU, consistent with previous inferences for A<0 and larger than that determined in the inner helio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 26 publications
(26 reference statements)
2
18
0
Order By: Relevance
“…• Anomalous fluxes of oxygen, nitrogen, and neon were observed along the Ulysses trajectory and at Earth and with spatial gradients different from galactic CRs (e.g., Heber and Marsden, 2001;Cummings et al, 2009).…”
Section: Samples From the Inner Heliospherementioning
confidence: 97%
“…• Anomalous fluxes of oxygen, nitrogen, and neon were observed along the Ulysses trajectory and at Earth and with spatial gradients different from galactic CRs (e.g., Heber and Marsden, 2001;Cummings et al, 2009).…”
Section: Samples From the Inner Heliospherementioning
confidence: 97%
“…By separating the variations in radial distance and latitude (Bastian et al 1980;McKibben et al 1979) and approximating them with an exponential function (e.g. Cummings et al 2009), Eq. (2) can be rewritten as…”
Section: Gradient Calculationmentioning
confidence: 99%
“…Figure 3 compares modeled O* energy spectra at Earth ( r = 1 AU; θ = 90°) for both the qA < 0 (solid line) and qA > 0 (dashed line) HMF configurations. Shown for comparison are qA > 0 observations for O* at/near Earth from the SAMPEX (downward triangles) [from Hill et al , 2002] and SOHO (squares) [from Marsden et al , 1999] spacecraft and qA < 0 observations of the STEREO (dots) and the ACE (upward triangles) spacecraft [both from Cummings et al , 2009]. The computed spectra show the general characteristics of ACR spectra in the inner heliosphere, for example, an almost exponential decay in intensity above ∼10 MeV nuc −1 and the well‐known j ∝ E increase in intensity below ∼10 MeV nuc −1 caused by adiabatic energy losses.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Computed O* energy spectra at Earth ( r = 1 AU; θ = 90°) for the qA > 0 (solid line) and qA < 0 (dashed line) HMF polarity cycles. For comparison O* observations at/near the Earth in the qA > 0 cycle, made by the SAMPEX (downward triangles) [from Hill et al , 2002] and SOHO (squares) [from Marsden et al , 1999] spacecraft and qA < 0 observations of the STEREO (dots) and the ACE (upward triangles) [both from Cummings et al , 2009] spacecraft are shown.…”
Section: Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation